CALCULATION OF PARAMETERS OF HYDRODYNAMICALLY STABLE EARTH DUCTS - S.S. Eshev; M.I. Rakhmatov; A.R. Rakhimov (International Journal on Orange Technologies, 2020)
The article describes the calculation of the parameters of soil-channel channels with hydrodynamic stability. It provides formulas to calculate the width and depth of water in large channels with hydrodynamically strong earth channels using existing studies.